RESTRICTIONS ON THE RELIGIOUS JUDICIARYS’ AUTHORITY AS A RESULT OF JUDICIAL POWER CONFLICT RULES - Rahadi Wasi Bintoro (Jurnal Dinamika Hukum, 2015)
The new authorities of religious courts, particularly in Economics Sharia field still collide with other rules. This writing intends to identify the rules conflict  that exist. Based on the analysis, can be identified the rule conflict  relating to the authority of the judge occurs on the peace effort. Rules of conflict regarding peace with instrument PerMA No.1 year 2008 can be accessed by using the principle of lex superior derogat legi law priori, whereas with regard to the authority prosecuting Sharia Board of arbitration verdict temporarily can use the verdict of the Supreme Court of Cassation Number 56/PK/AG/2011, however this is still not final because we are not wedded to the binding force principle of precedent. The next rule of conflict is related with judgement authority to the bankruptcy matter. On this occasion, the author gives suggestions to immediately syncronize authorities prosecutes’ rules, so it can give birth to legal certainty. Keyword: authority to prosecute, peace, The National Syariah Board Of Arbitration, bankruptcy